The Pan-African Parliament’s Unfinished Legislative Mandate and the Sovereignty Challenge of Its Continental Legislative Diplomacy - Zhizhi Meshach Rizama; Abah Innocent; Zhizhi Emmanuel Jiruma (JED (Jurnal Etika Demokrasi), 2026)
This study examines how the Pan-African Parliament (PAP) exercises legislative diplomacy without formal legislative authority, why African Union member states withhold ratification of the 2014 Malabo Protocol, and what this reveals about sovereignty and regional integration. Employing a qualitative case study design, the research analyzes 67 documents including official AU and PAP records, member state communications, and academic literature spanning 2004 to 2025. Through thematic analysis and qualitative content analysis using deductive and inductive coding, the study identifies three key findings. First, the PAP has developed a modality of "functional supranationalism," exercising practical influence via election observation, model law production, oversight hearings, and inter-parliamentary advocacy despite lacking binding legislative powers. Second, member states deploy "ratification sovereignty" strategically withholding ratification while sustaining budgetary and electoral engagement to preserve national leverage and avoid binding authority transfer. Third, the PAP's trajectory reveals that African integration proceeds through hybrid functional arrangements rather than constitutional supranationalism. The study contributes to theories of legislative diplomacy and treaty politics by demonstrating that parliamentary influence can accumulate through functional authority and norm entrepreneurship without formal competence, and by conceptualizing non-ratification as an active diplomatic resource rather than a passive procedural delay.